Insertion (4;11)(q27;q24q21) in a patient with essential thrombocythemia with progression to myelofibrosis - Gargallo, Patricia Martha (2004)
We report a case of essential thrombocythemia (ET) in a 39-year-old woman who developed myelofibrosis at follow-up. The cytogenetic and fluorescence in situ hybridization analyses revealed a pathologic clone with the following previously unreported karyotype: 46,XX,ins(4;11)(q27;q24q21). We cannot conclude that the presence of this inverted insertion was associated with the overproduction of platelets, but documentation of more cases with chromosomal abnormalities and ET should lead to identifying different candidate genes involved in the neoplastic growth.